Improved information flow topology for vehicle convoy control - 1979-, author; Shahdan Sudin, supervisor; Zaharuddin Mohamed, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2018